Determining optimal pacing strategy for the track cycling individual pursuit event with a fixed energy mathematical model - Underwood, L.; Jermy, M. (Sports Engineering, 2014)
Competitive track cycling races are won by milliseconds, and the regulation of an athlete`s power output is an important factor in performance. The aim of this study was to use a mathematical model to predict finishing times for different pacing strategies for the individual pursuit (IP), to identify the optimal strategy in terms of fastest finishing time. Power profiles were generated for a number of common pacing strategies used in cycling, which were based on actual SRM power data for an elite, male, IP cyclist for whom the average power, maximum power, total work done and actual finishing time were known. The total work output was the same for all strategies and the finishing time was predicted using a mathematical model developed previously. The results showed that, of the strategies tested, an initial "all-out" high power acceleration phase followed by a lower constant power output produced the fastest finishing time for a 4,000 m IP event, and that the time spent in the initial high power acceleration phase had a significant effect on performance.